Platform Engineering as a Service: Streamlining Developer Experience in Cloud Environments - Allam, Hitesh (International Journal of Emerging Research in Engineering and Technology, 2022)
Developers have more difficulty building, deploying, and running apps across many other environments in the modern, fast evolving cloud-native world. Platform Engineering as a Service (PEaaS) offers a coherent, self-service platform layer that eliminates infrastructure complexity and improves the software delivery lifecycle, therefore addressing this discrepancy. By means of their automation of common procedures, standard promotion, and faster, more consistent deployment facilitation, this article investigates how PEaaS enhances the developer experience. Through shifting the focus from infrastructure management to value creation via code, PEaaS helps development teams create with more speed and more reliability. The main goal of this work is to clarify the benefits and the challenges of using PEaaS in actual world cloud environments by means of case study and comparative analysis of companies adopting this strategy. Our approach integrates DevOps processes, developer productivity metrics, and a thorough review of platform engineering approaches. The findings show that PEaaS improves alignment between development and operations teams and reduces cognitive load and operational overhead for developers. Organizations often report as major outcomes improved time-to market, higher system reliability, and their better governance. The results highlight how strategically important platform engineering is becoming as a means of enabling scalable and sustainable cloud operations. Declaring that PEaaS is a necessary component in modern DevOps transformation and digital acceleration initiatives, this essay advocates a developer-oriented approach for platform architecture